Preventive Penalization in China: Background, Adverse Impact and Judicial Restriction - Zhou, Zhenjie (Magyar Rendészet, 2021)
Recent criminal law reforms in China show a noticeable preventive character by criminalizing preparatory activities, lowering conviction threshold and imposing crime prevention obligation on legal persons, especially internet service providers. Timely preventive penalization is necessary because it responds to requirement of modern society to prevent invisible yet destructive risks in almost every corner of industrial activities. Meanwhile, preventive penalization puts criminal law and citizens in danger too, because punishing formally unlawful conducts that cause no harm to society leads to not only injustice in criminal justice but also ineffective allocation of precious resources. Chinese legislation gives enough space and choices to judiciary to prevent adverse impact of preventive penalization in practice. Unfortunately, the absence of a common recognition of its obligation and collective action shows that there is still a long way to go before establishment of a check and balance mechanism between seemingly unstoppable preventive penalization and criminal justice.